ChemInform Abstract: Enantioselective Synthesis and Cross‐Coupling of Tertiary Propargylic Boronic Esters Using Lithiation—Borylation of Propargylic Carbamates. Issue 15 (25th March 2013) - Partridge, Benjamin M.; Chausset‐Boissarie, Laetitia; Burns, Matthew; Pulis, Alexander P.; Aggarwal, Varinder K.
Abstract Changing from pinacol to neopentyl glycol to ethylene glycol the enantioselectivities increase.